PENGARUH KOMPETENSI DAN INDEPENDENSI TERHADAP KUALITAS AUDIT DENGAN ETIKA AUDITOR SEBAGAI VARIABEL MODERSI - Ahmad Zainudin, 13.05.52.0211; Himmawan, Arief (Students Journal of Accounting and Banking, 2018)
The purpose of this study is to examine the influence of competence and independence on the quality of auditors with auditor ethics as an intervening variable. The sampling technique used in this study is the convenience sampling / sample selected with consideration of convenience. This is because there are some limitations, because not all the KAP contained in Semarang, Solo and Daerah Istimewa Yogyakarta can be visited and obtained data for research. The result of the research shows that Independence has negative effect not significant to audit quality in KAP in Central Java. Competence has no significant negative effect on audit quality with auditor ethics as moderating variable in KAP in Central Java. Independence has a significant positive effect on audit quality with auditor ethics as moderating variable in KAP in Central Java.Keywords: Audit Quality, Competence, Independence, and Auditor Ethics